Hubungan Kehamilan Post Date Dengan Kejadian Asfiksia Neonatorum Di RSIA Husada Bunda Salo - Masriah, Masriah; Handayani, Fitri; Miftahurrahmi, Miftahurrahmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Asphyxia neonatorum is a condition where a newborn baby (neonate) cannot begin to breathe spontaneously after birth. Several factors that cause neonatal asphyxia include maternal, infant and umbilical cord factors. The aim of this research was to determine the relationship between Post Date pregnancies at RSIA Husada Bunda in 2022. This type of research used analytical observational using a Case Control research design with a Retrospective approach. The population in this study used a 1:1 ratio of case samples (neonatal asphyxia) and 50 control cases (no neonatal asphyxia). Control samples were taken using systematic random sampling. The data collection tool in this research used a checklist sheet. Then the data was analyzed Univariately and Bivariately using the chi square test. The results of this research showed that there was a relationship between post-date pregnancy and the incidence of neonatal asphyxia with p value (0.002). The conclusion was that there was a relationship between post-date pregnancy and the incidence of neonatal asphyxia at RSIA Husada Bunda in 2022. It is hoped that the results of this research will provide an illustration for health workers and policy makers as material for consideration, information and decision making for the management of newborns with neonatal asphyxia.